Lessons learned and policy implications from an organizational reform of the World Health Organization African region country offices: a policy brief - Usman, Abdulmumini; Cabore, Joseph; Olu, Olushayo Oluseun; Ba, Ndoungou Salla; Kabore, Patrick; Okeibunor, Joseph; Gasasira, Alex; Moeti, Matshidiso (Frontiers in Public Health, 2025)
A decade ago, the World Health Organization (WHO) faced global calls for significant reforms to shift its focus from donor-driven priorities to those determined by its Member States. This demand was driven by political and financial pressures aimed at enhancing effectiveness and efficiency in service delivery. The WHO Regional Office for Africa was particularly challenged, and the 2014–2015 Ebola outbreak further amplified the need for transformative changes. In response, the World Health Organization Regional Director launched the Transformation Agenda in 2015, aiming to improve the organization’s efficiency and responsiveness. Within this reform agenda, a major restructuring of the 47 World Health Organization Country Offices, known as the Functional Review, was conducted between 2017 and 2019. This article reflects on the experiences and lessons from the Functional Review process, providing insights, policy options, and recommendations for future reforms. Key lessons from the Functional Review include the need for sufficient resources, stakeholder engagement, flexibility, and clear communication during organizational reforms.